Community-Based School for the Control and Remission of Type 2 Diabetes - Carlos Regino Alejandro Polanco; María Alejandra Rivadeneira Lucas; Cindy Giselle Díaz Contino; María Verónica Vega Roldan; Glen Neptalí Guerrero Arias; Frank Stalin Vinces Vinueza (Journal of Health Science and Medical Therapy, 2026)
Recent research suggests that type 2 diabetes mellitus (T2DM) is potentially reversible, positioning non-pharmacological interventions as a central component of clinical treatment. Accordingly, the present study aimed to evaluate the effectiveness of a community-based school as an educational and community intervention strategy to achieve remission or metabolic control in patients with T2DM in a rural setting in Ecuador. A quasi-experimental pretest-posttest study without a control group was conducted with a sample of 24 patients with T2DM from a rural community in Manabí, Ecuador, who participated for 11 months in a community-based school structured around educational sessions and practical activities. Variables such as T2DM remission, metabolic control, and adherence to the program were assessed. Data were analyzed using descriptive and inferential statistics with the support of the Statistics Stats software. At the end of the intervention, 37.5% of participants achieved clinical remission of T2DM without the use of medication, and 58.33% reached metabolic control with treatment. Clinical complications persisted in 25.0% of the cases (95% CI: 12.0%–44.9%). These results suggest that a culturally adapted, comprehensive educational approach can effectively reverse or manage type 2 diabetes and does not depend on the participant’s formal educational level to be effective.